Developing Subsidized Mortgage Agreement Based on the Justice Values of Pancasila (Indonesian State Philosophy) - KUSUMASTUTI, Dora (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The objectives of this research are to investigate the implementation of subsidized mortgage agreement and to develop subsidized mortgage agreement based on the justice values of Pancasila through the development of a model of subsidized mortgage agreement. The research used descriptive method with the interactional/micro approach with qualitative analysis. The sources of data were interview and forum group discussion. The data were collected through in-depth interview and observation. They were validated by means of the source and method triangulations. They were then analyzed by using the interactive model of analysis. The result of research shows that the subsidized mortgage agreement drawn up in a standardized format by banks makes the consumers of subsidized mortgage in a fragile position when dealing with banks which provide the services to fulfill their desire to have houses. The subsidized mortgage agreement currently has not been based on the basic values of Pancasila, and therefore a model of subsidized mortgage agreement as an elaboration of the values of Pancasila is required.